The Janus faced teacher educator - Smith, Kari (2019)
This paper focuses on the Janus face-teacher educator and researcher. Drawing on existing international literature, our aim is to position ourselves in the discussion relating to our own and other research. In this paper we limit ourselves to discuss two main components, namely teaching and research in relation to which teacher educators seem to experience a rather strong tension. We maintain that the quality of teaching does not become inferior to research and publishing in teacher education. This necessitates that sufficient resources are provided for assuring the quality of teaching and for research; subsequently the two activities are complementary and not contradictory to each other. Our claim is that teacher educators in most settings are Janus-faced due to the competing demands of excellence in both research and teaching. However, we strongly believe that the two main responsibilities of teacher educators which form the Janus face, can melt into each other in the face of a researching teacher educator.